Celiac disease and metabolic syndrome: from risk to a preventive opportunity, in the perspective of children’s health - Zuccotti, Gianvincenzo; Calcaterra, Valeria; Rossi, Virginia; Vincenti, Alessandra; Loperfido, Federica; Baldassarre, Paola; Maccarini, Beatrice; Fasano, Alessio; Cena, Hellas (Frontiers in Nutrition, 2026)
BackgroundCeliac disease (CD) is a chronic immune-mediated enteropathy triggered by gluten ingestion in genetically predisposed individuals and is increasingly diagnosed in childhood. Growing evidence suggests an association between CD and metabolic syndrome (MetS), potentially mediated by chronic inflammation, intestinal dysbiosis, oxidative stress, and micronutrient deficiencies. In addition, although a gluten-free diet (GFD) is essential for intestinal recovery, its frequent reliance on ultra-processed, energy-dense products may adversely affect metabolic health, particularly in pediatric patients.ObjectiveThis narrative review aims to examine the relationship between CD and MetS, with a specific focus on pediatric populations, by analyzing shared pathophysiological mechanisms, the metabolic impact of a GFD, and preventive nutritional strategies to reduce long-term cardiometabolic risk.MethodsA narrative review was performed using PubMed and Scopus databases, focusing on studies published in the past 15 years. Search terms included “Celiac Disease,” “Metabolic Syndrome,” “Child,” “Adolescent,” “Risk Factors,” and “Prevention.” Among 229 identified papers, 43 were selected after critical appraisal. Evidence was synthesized on epidemiology, mechanisms, dietary effects, and preventive strategies.ResultsStudies indicate that MetS prevalence in CD ranges from 3 to 11% at diagnosis and may rise to 14–29% after 1 year on a GFD, particularly in adults. In children, complete MetS is rare, though isolated components, central adiposity, dyslipidemia, and hypertension, are increasingly observed. Mechanistically, gluten-induced barrier disruption, inflammation, dysbiosis, and nutritional imbalances contribute to systemic metabolic alterations. Adherence to a Mediterranean-style GFD emphasizing whole, naturally gluten-free foods reduces cardiometabolic risk.ConclusionCD and MetS share interconnected inflammatory and metabolic pathways. While GFD remains essential for CD management, it necessitates tailored nutritional guidance and metabolic monitoring. Early lifestyle-based interventions—promoting balanced diet quality, micronutrient adequacy, and physical activity, offer key opportunities to prevent metabolic complications in children with CD.